A Unique Model System for Tumor Progression in GBM Comprising Two Developed Human Neuro-Epithelial Cell Lines with Differential Transforming Potential and Coexpressing Neuronal and Glial Markers - Anjali Shiras; Arti Bhosale; Varsha Shepal; Ravi Shukla; V.S. Baburao; K. Prabhakara; Padma Shastry (Neoplasia: An International Journal for Oncology Research, 2003)
The molecular mechanisms involved in tumor progression from a low-grade astrocytoma to the most malignant glioblastoma multiforme (GBM) have been hampered due to lack of suitable experimental models. We have established a model of tumor progression comprising of two cell lines derived from the same astrocytoma tumor with a set of features corresponding to low-grade glioma (as in HNGC-1) and high-grade GBM (as in HNGC-2). The HNGC-1 cell line is slowgrowing, contact-inhibited, nontumorigenic, and noninvasive, whereas HNGC-2 is a rapidly proliferating, anchorage-independent, highly tumorigenic, and invasive cell line. The proliferation of cell lines is independent of the addition of exogenous growth factors. Interestingly, the HNGC-2 cell line displays a near-haploid karyotype except for a disomy of chromosome 2. The two cell lines express the neuronal precursor and progenitor markers vimentin, nestin, MAP-2, and NFP160, as well as glial differentiation protein S100μ. The HNGC-1 cell line also expresses markers of mature neurons like Tuj1 and GFAP, an astrocytic differentiation marker, hence contributing toward a more morphologically differentiated phenotype with a propensity for neural differentiation in vitro. Additionally, overexpression of epidermal growth factor receptor and c-erbB2, and loss of fibronectin were observed only in the HNGC-2 cell line, implicating the significance of these pathways in tumor progression. This in vitro model system assumes importance in unraveling the cellular and molecular mechanisms in differentiation, transformation, and gliomagenesis.